Animation of human diving - Wooten, W. L.; Hodgins, J. K. (Computer Graphics Forum, 1996)
The motion of a human platform diver was simulated using a dynamic model and a control system. The dynamic model has 32 actuated degrees of freedom and dynamic parameters within the range of those reported in the literature for humans. The control system uses algorithmsfor balance, jumping, and twisting to initiate the dive, sequences of desired values for proportional-derivative servos to perform the aerial portion of the dice, and a state machine to sequence the actions throughout the dice. The motion of the simulated diver closely resembles video footage of dices performed by human athletes. The control and simulation techniques presented in this paper are useful for providing realistic motion for synthetic actors in computer animations and virtual environments and may someday be useful for analysis of sports performance.